Design and Enantioselective Synthesis of Cashmeran Odorants by Using "Enol Catalysis"1. Issue 6 (8th January 2015) - Felker, Irene; Pupo, Gabriele; Kraft, Philip; List, Benjamin
Abstract Novel Cashmeran odorants were designed by molecular modeling. Their short syntheses involve a novel asymmetric Brønsted acid catalyzed Michael addition of unactivated α‐substituted ketones. This key transformation was realized by utilizing a new type of enol activation catalysis and affords different cyclic ketones bearing α‐quaternary stereocenters in good to excellent yields and with high enantioselectivity. Subsequent McMurry coupling and Saegusa–Ito oxidation furnished the enantiopure target odorants, one enantiomer of which indeed possesses the typical olfactory aspects of Cashmeran.